(untitled) (Journal of Organizational Psychology, 2022)
Professional burnout can be a significant problem for the public accounting industry. Identifying the tendency to burnout can possibly help identify solutions. The purpose of this correlational quantitative study was to examine the relationship between gender, age, and emotional exhaustion (EE) related to burnout in a large, national public accounting firm in the United States. EE is defined as a feeling of excessive emotional stress and being drained by contact with other people. The results of the study indicated that the combination of both age and gender resulted in a statistically significant regression model. Analysis indicated that young, female professionals are more likely to experience EE. The investigation indicated that additional independent variables might more reliably predict the emotional exhaustion within the surveyed population.